"PAIKEM GEMBROT IN ENGLISH LANGUAGE TEACHING FOR YOUNG LEARNERS: A NARRATIVE INQUIRY OF TEACHERS' EXPERIENCE" - Henny Dwi Iswati; Nilam Kis Arumecendani Rois (Wiralodra English Journal, 2023)
This research looks into the use of the Paikem Gembrot model as a method of teaching English to young learners. The study aims to understand the challenges and efforts of kindergarten teachers regarding the Paikem Gembrot method in introducing English to young learners. The study employed a narrative inquiry approach, using a narrative frame to gather data from 40 kindergarten teachers in East Java. The findings show that those teachers have positive perceptions of the Paikem Gembrot model and believe it to be successful in promoting English language learning among young learners. However, they also identified some challenges such as a lack of understanding of the concept, insecurity, lack of appropriate learning tools and media, lack of teacher skills in managing the class, the low attention span of children, and the young age factor. The teachers have been involved in seminars, sharing experiences with other teachers, and learning from various media. They also suggested the development of simple and widely accessible learning tools and carrying out activities with a cheerful tone to address the technical issues.